Depuration of live oysters to reduce Vibrio parahaemolyticus and Vibrio vulnificus: A review of ecology and processing parameters. Issue 4 (31st May 2022) - Campbell, Vashti M.; Chouljenko, Alexander; Hall, Steven G.
Abstract: Consumption of raw oysters, whether wild‐caught or aquacultured, may increase health risks for humans. Vibrio vulnificus and Vibrio parahaemolyticus are two potentially pathogenic bacteria that can be concentrated in oysters during filter feeding. As Vibrio abundance increases in coastal waters worldwide, ingesting raw oysters contaminated with V. vulnificus and V. parahaemolyticus can possibly result in human illness and death in susceptible individuals. Depuration is a postharvest processing method that maintains oyster viability while they filter clean salt water that either continuously flows through a holding tank or is recirculated and replenished periodically. This process can reduce endogenous bacteria, including coliforms, thus providing a safer, live oyster product for human consumption; however, depuration of Vibrio s has presented challenges. When considering the difficulty of removing endogenous Vibrios in oysters, a more standardized framework of effective depuration parameters is needed. Understanding Vibrio ecology and its relation to certain depuration parameters could help optimize the process for the reduction of Vibrio . In the past, researchers have manipulated key depuration parameters like depuration processing time, water salinity, water temperature, and water flow rate and explored the use of processing additives to enhance disinfection in oysters. In summation, depuration processing from 4 to 6 days, low temperature, high salinity, and flowing water effectively reduced V. vulnificus and V. parahaemolyticus in live oysters. This review aims to emphasize trends among the results of these past works and provide suggestions for future oyster depuration studies.